(untitled) (Ideal Journal of Multidisciplinary Research, 2026)
This article analyzes the financial stability of “UZTRANSGAZ” JSC by evaluating its main financial indicators to assess the company’s current financial condition. It also proposes potential measures to mitigate financial risks and strengthen long-term stability. The analysis is conducted using key financial assessment methods, including liquidity, profitability, and efficiency ratios.